KEBIJAKAN LINGKUNGAN DI PROYEK GAS BUMI: ANALISIS DENGAN TEORI HUKUM DAN PEMBANGUNAN BURG - Kaleresan, Nurita; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This paper discusses environmental policies in natural gas projects and analyzes them using the concepts of Law and Development of Theory Burg. Environmental policies in natural gas projects are crucial to ensure the use of clean and reliable energy sources while considering the environmental and social impacts and efforts to prevent or reduce those impacts. In this analysis, the author highlights the importance of maintaining stability, predictability, fairness, education, and the special development abilities of the lawyer in developing environmental policies that comply with regulations and meet legal requirements related to natural gas projects. Overall, this document underscores the significance of incorporating the Law and Development Theory by Burg into the environmental policies governing natural gas projects in Indonesia. By referring to these principles, it is expected that environmental policies can maintain ecosystem stability, prediction and mitigate environmental impacts, provide fair treatment to affected communities, enhance understanding and awareness through education, and integrate relevant legal aspects through the specialized role of legal experts.Keywords: environmental policies, natural gas projects, Law and Development Theory Burg